Effect of Flooding and the nosZ Gene in Bradyrhizobia on Bradyrhizobial Community Structure in the Soil - Saeki, Yuichi (Microbes Environ, 2017)
We investigated the effects of the water status (flooded or non-flooded) and presence of the nosZ gene in bradyrhizobia on the bradyrhizobial community structure in a factorial experiment that examined three temperature levels (20°C, 25°C, and 30°C) and two soil types (andosol and gray lowland soil) using microcosm incubations. All microcosms were inoculated with Bradyrhizobium japonicum USDA6(T), B. japonicum USDA123, and B. elkanii USDA76(T), which do not possess the nosZ gene, and then half received B. diazoefficiens USDA110(T)wt (wt for the wild-type) and the other half received B. diazoefficiens USDA110ΔnosZ. USDA110(T)wt possesses the nosZ gene, which encodes N(2)O reductase; 110ΔnosZ, a mutant variant, does not. Changes in the community structure after 30- and 60-d incubations were investigated by denaturing-gradient gel electrophoresis and an image analysis. USDA6(T) and 76(T) strains slightly increased in non-flooded soil regardless of which USDA110(T) strain was present. In flooded microcosms with the USDA110(T)wt strain, USDA110(T)wt became dominant, whereas in microcosms with the USDA110ΔnosZ, a similar change in the community structure occurred to that in non-flooded microcosms. These results suggest that possession of the nosZ gene confers a competitive advantage to B. diazoefficiens USDA110(T) in flooded soil. We herein demonstrated that the dominance of B. diazoefficiens USDA110(T)wt within the soil bradyrhizobial population may be enhanced by periods of flooding or waterlogging systems such as paddy–soybean rotations because it appears to have the ability to thrive in moderately anaerobic soil.